Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bali Summer Restaurant Kuta - Kusuma, Made Adiguna; Nurcahya, Ketut (E-Jurnal Manajemen; Vol 2 No 6 (2013), 2013)
The purpose of this study was to determine the effect of the quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy simultaneously and partially on customer satisfaction in Summer Restaurant Kuta Bali. The research was conducted in Summer Restaurant Kuta Bali, which is located at Jl. No. Kuta Beach. 38, Br. Pande Mas, Kuta, Badung - Bali. The variables studied were the quality of service, namely tangibles, responsiveness, reliability, assurance and empathy. The second variable is customer satisfaction. Purposive sampling technique used to get 120 respondents. The data analysis technique used is multiple linear regression analysis techniques. The results showed that: the quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy simultaneously and partially positive and significant impact on customer satisfaction Summer Restaurant Kuta Bali. The results of this study provide practical implications that management Summer Restaurant Kuta Bali is expected to maintaining empathy variable consisting of good communication, patient and hospitality employees. Keywords: service quality, satisfaction